Environmental Challenges in Today's Iran. Issue 6 (November 2016) - Amanat, Abbas; Tahbaz, Morad; Bayani, Niloufar; Cole, Camille; Tahbaz, Morad
Abstract : Drought, increased population, war, air pollution, climate change, industrial and agricultural production, sanctions, inefficient water and natural resource use, and lack of enforcement of existing environmental regulations have contributed to Iran's current environmental crisis. Insufficient water resources are forcing people to migrate, putting pressure on others. Aquifers are being drained. Air pollution has made living conditions in Iran's cities increasingly challenging. Wind erosion is furthering the desertification of agricultural land, creating greater production demand on remaining arable areas. Biodiversity is under threat. On the other hand, Iran's environmental future can be positively influenced by the collaboration of the public, private and non-profit sectors. Awareness and education, along with greater financial and human resources, will be necessary to tackle the problem.